Air monitoring system using Arduino (Eurasian Journal of Research, Development and Innovation, 2024)
Air quality is one of the main factors that determine health. the human need for clean air is something that cannot be underestimated. because the number of sources of air pollutants everywhere is different. air pollution is a simple thing, but it is extremely dangerous if it is allowed to continue. so we need a monitoring tool to monitor air pollutants and the results can be monitored in real time. this is a device that measures the levels of carbon dioxide, nitrogen, benzene, methane and smoke by a gas sensor, indoor and outdoor temperatures, and humidity by a temperature sensor and controlled using an arduino processor. the light is red and it is a warning